Drivers and intensity of beekeeping adoption: Micro-evidence from Berekum, Ghana - Prince Asiedu; Lovenger Appiah (Scientific African)
Beekeeping is increasingly promoted as a livelihood diversification strategy in rural Ghana, yet smallholder farmers face significant challenges in sustaining and expanding their beekeeping enterprises. Understanding the factors that drive adoption and influence the intensity of participation is essential for designing effective interventions. This study investigates the drivers of beekeeping adoption and the extent of participation among smallholder farmers in Berekum, Ghana, while identifying key barriers that limit its expansion. Despite the recognized benefits of beekeeping, including income generation and ecological services, adoption remains limited due to socio-economic and environmental constraints. Using data from a cross-sectional survey of 230 farmers, comprising 94 adopters and 136 non-adopters, the study employed the Heckman two-step model to account for potential selection bias when analyzing the decision to adopt beekeeping and the number of beehives managed. The analysis revealed that membership in farmer-based organizations, honey utilization for home consumption, and farming experience significantly increased the likelihood of adoption and the scale of participation. However, capital constraints, lack of honey processing equipment, deforestation, limited bee flora, pests, bee abscondment, and climate variability were major barriers affecting adoption intensity. The findings inform the critical role of institutional support, particularly access to financial resources and infrastructure, in enhancing beekeeping adoption and sustainability. Addressing these constraints through targeted policy interventions, such as improving rural credit access, investing in processing facilities, and promoting environmental conservation, is essential for scaling up smallholder apiculture as a viable livelihood strategy. These insights contribute to the holistic understanding of the adoption dynamics of beekeeping in rural contexts, offering evidence-based recommendations for development practitioners and policymakers aiming to enhance rural incomes and ecological resilience through apiculture.